Resonant waveguide grating biosensor-enabled label-free and fluorescence detection of cell adhesion - Zaytseva, Natalya (2013)
Cell adhesion to extracellular matrix (ECM) is fundamental to many distinct aspects of cell biology, and has been an active topic for label-free biosensors. However, little attention has been paid to study the impact of receptor signaling on the cell adhesion process. We here report the development of resonant waveguide grating biosensor-enabled label-free and fluorescent approaches, and their use for investigating the adhesion of an engineered HEK-293 cell line stably expressing green fluorescent protein (GFP) tagged β(2)-adrenergic receptor (β(2)-AR) onto distinct surfaces under both ambient and physiological conditions. Results showed that cell adhesion is sensitive to both temperature and ECM coating, and distinct mechanisms govern the cell adhesion process under different conditions. The β(2)-AR agonists, but not its antagonists or partial agonists, were found to be capable of triggering signaling during the adhesion process, leading to an increase in the adhesion of the engineered cells onto fibronectin-coated biosensor surfaces. These results suggest that the dual approach presented is useful to investigate the mechanism of cell adhesion, and to identify drug molecules and receptor signaling that interfere with cell adhesion.